Circadian and lunar patterns of Jaguar and Puma in relation to their prey and competitors (UNED Research Journal, 2021)
Introduction: Temporal niche changes can shape predator-prey interactions by allowing prey to evade predators, improve feeding efficiency, and reduce competition among predators. In addition to circadian activity patterns, the monthly lunar cycle can influence the nocturnal activity of mammals. Objective: Through camera trap surveys at sites on the Pacific slope and the Talamanca Cordillera, we investigated the patterns of circadian (day and night) and nocturnal activity during the moon phases of the jaguar (Panthera onca) and puma (Puma concolor). Methods: We investigated the overlap and temporal segregation between pairs of each predator and its primary prey, and between its competitors using overlap analysis, circular statistics, and relative abundance, taking into account differences in habitat, seasons, and human impact between sites. Results: Our results supported the existence of a temporal niche separation between the two predator species, although both were classified as cathemeral - the jaguar was mainly diurnal, while the puma was mainly nocturnal. We found that the jaguar and puma practice different patterns of nocturnal activity during the phases of the moon, with the jaguar exhibiting a dramatic increase in activity during the full moon and the puma maintaining a more consistent level of activity throughout the moon phases. However, during the full moon, both species were more active at night and less active during the day, suggesting that they practice a temporary niche change to take advantage of hunting activities during the brightest lunar illumination of each month. We discuss predicted primary prey and competing species. Conclusion: We conclude that jaguar and puma exhibit significant niche separation in circadian and lunar activity patterns. Through these differences in temporal activity, jaguar and puma can exploit a slightly different prey base despite their similar large size.
Keywords: activity patterns; predator-prey; temporal niche change; circadian; moon phases